Wage inequality, labor income taxes, and the notion of social status - Ennio Bilancini; Leonardo Boncinelli (Economics: The Open-Access, Open-Assessment E-Journal, 2019)
The authors investigate the desirability of income taxes when the objective is to mitigate wasteful conspicuous consumption generated by people's status-seeking behavior. They consider the joint role of pre-tax wage inequality and of social norms determining how social status is assigned. They find that when social status is ordinal (i.e., only one's rank in the income distribution matters) inequality and taxation are substitutes. Instead, when status is cardinal (i.e., also the shape of the income distribution matters) inequality and taxation can be complements, although the relationship is in general non-monotonic. This is because the value of social status is endogenous, potentially giving rise to a perverse self-reinforcing mechanism where more waste in conspicuous consumption induces a greater competition for status and viceversa.
Keywords: D6; H3; J2; 330; social status; relative standing; consumption externalities; labor income; income tax; signalling; conspicuous consumption; income inequality